Trade unions and European integration: a question of optimism and pessimism? (Abingdon, 2019)
"Trade Unions under the Pressure of European Integration brings together pessimists and optimists on trade unionism under the contemporary pressures of European integration. The Great Recession has brought new attention to structural problems of the European integration process, specifically monetary integration; holding the potential of disabling any trans-national co-ordination. Other authors argue that the current crisis also poses the chance for mobilization and new impulses for European trade unionism. This is discussed in the volume alongside a variety of topics including bargaining coordination, co-determination, European governance regimes, and European wide mobilization.